Energy-saving and long-life carbon crucible and preparation method thereof

By forming a three-dimensional network structure of C-V2AlC in the carbon crucible, the problem of carbon crucible consumption of a large amount of carbon resources and short life is solved, efficient utilization and environmental protection and energy saving are achieved, and the thermal shock stability and industry of the product are improved. Competitiveness.

CN116903372BActive Publication Date: 2024-12-13JIANGSU TAIRUI REFRACTORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310832446.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2024-12-13
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

The existing carbon crucibles consume a large amount of carbon resources at high temperatures, and have short service life and high energy consumption, which cannot effectively solve the problems of efficient utilization of carbon resources and environmental protection and energy conservation.

Method used

Energy-saving and long-lived carbon crucible made of carbon crude aggregate, fine aggregate, fine powder, tempering additive and water-soluble bonding agent, and form a three-dimensional network structure of C-V2AlC through high-temperature carbonization to enhance resistance Erosion ability and toughness, and chemical bonds between carbon aggregate and matrix to improve thermal shock stability.

Benefits of technology

It significantly improves the service life and thermal shock stability of carbon crucibles, reduces carbon emissions and production costs, improves industrial competitiveness, and reduces raw material consumption and wettability, and improves the comprehensive mechanical properties of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium battery production, and in particular to an energy-saving and long-life carbon crucible and a preparation method. An energy-saving and long-life carbon crucible is prepared by high-temperature carbonization of the following raw materials by weight: 10 to 50 parts of carbon coarse aggregate, 20 to 35 parts of carbon fine aggregate, 15 to 40 parts of carbon fine powder, 0.01 to 3 parts of quenching and tempering additives, and 3 to 25 parts of water-soluble binders; the modulated additives are composed of aluminum powder, vanadium powder, vanadium carbide and benzopyrene. A composite binder and a modulated additive are mixed with carbon, and a three-dimensional network structure of C-V2AlC is formed inside the sagger during the roasting process to enhance the corrosion resistance. The coupling effect of the in-situ generated carbon fiber and the V2AlC with high damage tolerance further improves the toughness and thermal shock stability of the product, and increases its service life. The quenching and tempering additives play a role in promoting the graphitization of the carbon sagger, while improving its high temperature stability, reducing the wettability with the contents, saving energy and reducing emissions, and reducing production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery production, and in particular to an energy-saving and long-life carbon crucible and a preparation method thereof. Background Art

[0002] With the rapid development of the global new energy industry, there has been an unprecedented strong demand for new energy vehicles, energy storage equipment and consumer electronics, and the demand for carbon negative electrode materials has also increased significantly. As a key material for lithium-ion batteries, carbon negative electrode materials have gradually become the mainstream of the negative electrode material market, accounting for about 70% of the market share. The carbonization process of artificial carbon negative electrode materials is a key point affecting the quality of negative electrode materials and a technical difficulty. At present, there are many types of domestic carbonization equipment, high energy consumption, heavy pollution, and low degree of automation, which to a certain extent restricts the development of carbon negative electrode materials and is the main problem that needs to be solved in the current production process of negative electrode materials.

[0003] At present, there are four types of furnaces used in the carbonization process of negative electrode materials: Acheson carbonization furnace, internal series carbonization furnace, box-type carbonization furnace and continuous carbonization furnace. Among them, the most commonly used is the Acheson carbonization furnace, and a small amount of internal series carbonization furnace is used. The internal series carbonization furnace has the characteristics of high thermal efficiency and short power transmission time. The product has uniform resistance when directly heated, and the product yield is high.

[0004] However, the inner furnace crucible also serves as a heating element, and high quality requirements are placed on the carbon crucible. The dense structure and high thermal conductivity of existing carbon crucibles result in the consumption of a large amount of precious carbon resources, and the crucible cools down quickly and consumes high energy during service. These problems make it impossible to break through the key technical difficulties faced in the efficient utilization of carbon resources and environmental protection and energy conservation.

[0005] Therefore, we propose an energy-saving and long-life carbon crucible and a preparation method for solving the above problems. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an energy-saving and long-life carbon crucible and a preparation method thereof.

[0007] An energy-saving and long-life carbon crucible is prepared by high-temperature carbonization of the following raw materials in parts by weight:

[0008] 10-50 parts of carbon coarse aggregate, 20-35 parts of carbon fine aggregate, 15-40 parts of carbon fine powder, 0.01-3 parts of tempering additive, 3-25 parts of water-soluble binder;

[0009] The modulated additive consists of 20 to 30 parts by weight of aluminum powder, 40 to 60 parts by weight of vanadium powder, 50 to 70 parts by weight of vanadium carbide and 10 to 20 parts by weight of benzopyrene.

[0010] Preferably, the carbon aggregate includes carbon coarse aggregate and carbon fine aggregate, the carbon aggregate is one or more of low-carbon earthy graphite, conductive carbon black, activated carbon and asphalt, the particle size of the carbon coarse aggregate is 1mm to 3mm, and the particle size of the carbon fine aggregate is 0.08mm to 1mm.

[0011] Preferably, the carbon fine powder is one or more of low-carbon earthy graphite, conductive carbon black, activated carbon and asphalt, and the particle size of the carbon fine powder is 200-600 meshes.

[0012] Preferably, the water-soluble binder is one or more of furfural resin, epoxy resin-modified phenolic resin, arabic resin, lignin, polyvinyl alcohol and phosphate.

[0013] A method for preparing an energy-saving and long-life carbon crucible comprises the following steps:

[0014] S1. Add carbon fine powder and tempering additives into a high-speed mixer and premix for 15 minutes to 12 hours to obtain a batch material;

[0015] S2, loading the premixed batch materials in step S1 into a high-speed ball mill, adding 5% to 50% of the mass of the batch materials with deionized water into the high-speed ball mill, and then drying and granulating with a high-speed spray granulation equipment to obtain granulated materials;

[0016] S3, premix the carbon aggregate with one half of the water-soluble binder at 25°C to 200°C for 15min to 12h, add the granulated material prepared in step S2, mix at 25°C to 280°C for 15min to 12h, continue to add the remaining one half of the water-soluble binder, mix at the same temperature for 15min to 12h to obtain a uniform mixture;

[0017] S4, drying and trapping the mixture prepared in step S3 to obtain a formed mixture;

[0018] S5, putting the mixed material obtained in step S4 into an extruder to obtain a carbon crucible blank, and then isostatically pressing the ceramic tube blank obtained by extrusion molding to obtain a dense and uniform carbon crucible blank;

[0019] S6. Place the carbon crucible blank obtained in step S5 in a high-temperature furnace, keep it at 200°C to 400°C for 0.5h to 2h, and keep it at 800°C to 1200°C for 1h to 2h, and generate a three-dimensional network structure of C-V2AlC in situ to obtain a carbon crucible.

[0020] Preferably, in step S2, when spray drying granulation is performed, the wind temperature of the spray granulator is 150°C to 300°C, the particle size of the obtained granules is 0.001mm to 1.5mm, and then the granules are sealed and trapped at a temperature of 28°C to 32°C for 12h to 36h.

[0021] Preferably, in step S4, the conditions for drying the mixed material are: temperature 25°C to 350°C, humidity 1% to 15%, drying time 2h to 25h, and sealing time 12h to 48h.

[0022] Preferably, in step S5, the isostatic pressure is 150-200 MPa.

[0023] Preferably, in step S6, the high temperature furnace is one of an Acheson carbonization furnace, an inner-series carbonization furnace, a box-type carbonization furnace and a continuous carbonization furnace.

[0024] Preferably, in step S6, carbonization is carried out under the protection of vacuum, nitrogen, carbon-buried or argon atmosphere, and the temperature is increased to 200°C to 400°C at a heating rate of 5°C / h to 30°C / h, and then increased to 800°C to 1200°C at a heating rate of 10°C / h to 60°C / h.

[0025] The beneficial effects of the present invention are:

[0026] 1. A composite binder and a modulated additive are mixed with carbon. During the roasting process, a three-dimensional network structure of C-V2AlC is formed inside the sagger, filling the pores and forming a chemical bond between the carbon aggregate and the matrix, thereby enhancing the corrosion resistance of the carbon sagger. At the same time, the coupling effect of the in-situ generated carbon fiber and the V2AlC with high damage tolerance further improves the toughness and thermal shock stability of the product and increases its service life.

[0027] 2. The tempering additives added to the carbon crucible promote the graphitization of the carbon crucible, improve its high temperature stability and reduce the wettability with the contents, and the graphitization process continues during the use of the product. Related products can accelerate the pace of reducing carbon emissions in the carbon crucible industry, while reducing corporate production costs and improving the global competitiveness of the industry and economy.

[0028] 3. The crucible matrix with controllable microstructure is prepared by using different particle grading, and the high-solid phase slurry is mixed by a high-speed ball mill. The components of each ingredient have good dispersion and the components with large specific gravity difference are not easy to segregate. The dry powder is prepared by slurry spray granulation method. The composition and organization of each part of the product can be guaranteed to be uniform in both dry and wet molding.

[0029] 4. According to the needs of product use, the shape and thickness are determined and different molding methods are selected, which improves the density of the carbon crucible, improves the comprehensive mechanical properties and thermal shock stability of the product, greatly reduces the raw material consumption caused by machining, and greatly increases product profits for manufacturers. DETAILED DESCRIPTION

[0030] The present invention will be further explained below in conjunction with specific embodiments.

[0031] Embodiment 1:

[0032] An energy-saving and long-life carbon crucible is prepared by high-temperature carbonization of the following raw materials in parts by weight:

[0033] 20 parts of activated carbon coarse aggregate with a particle size of 1mm to 3mm, 25 parts of activated carbon fine aggregate with a particle size of 0.08mm to 1mm, 35 parts of activated carbon fine powder with a particle size of 200 to 600 mesh, 1.5 parts of conditioning additives, and 8 parts of furfural resin binder;

[0034] The additive preparation consists of 27 parts by weight of aluminum powder, 51 parts by weight of vanadium powder, 63 parts by weight of vanadium carbide and 12 parts by weight of benzopyrene.

[0035] A method for preparing an energy-saving and long-life carbon crucible comprises the following steps:

[0036] S1. Add activated carbon fine powder and conditioning additives into a high-speed mixer and premix for 45 minutes to obtain a batch material;

[0037] S2, the premixed batch material in step S1 is loaded into a high-speed ball mill, 40% of the mass of the batch material is added to the high-speed ball mill, and then dried and granulated by a high-speed spray granulation equipment, the air temperature of the spray granulator is 220°C, and the particle size of the granulated material is 0.8mm, and then the material is sealed and trapped at a temperature of 30°C for 24 hours to obtain the granulated material;

[0038] S3, premixing the activated carbon aggregate with half of the furfural resin binder at 80° C. for 30 min, adding the granulated material prepared in step S2, mixing at 100° C. for 30 min, continuing to add the remaining half of the furfural resin binder, mixing at the same temperature for 60 min, to obtain a uniform mixture;

[0039] S4, drying the mixture obtained in step S3 at a temperature of 180° C. and a humidity of 2% for 5 h, and sealing the mixture for 36 h to obtain a formed mixture;

[0040] S5, putting the mixed material obtained in step S4 into an extruder to obtain a carbon crucible blank, and then isostatically pressing the ceramic tube blank obtained by extrusion molding to obtain a dense and uniform carbon crucible blank, and the isostatic pressing pressure is 180MPa;

[0041] S6. The carbon crucible blank obtained in step S5 is placed in a high-temperature furnace, which is an internal series carbonization furnace. The carbonization is carried out under the protection of a nitrogen atmosphere, so that a layer of carbon nitride is formed on the surface of the sagger to improve the ability of the sagger to resist hydrogen corrosion. The temperature is increased to 300° C. at a heating rate of 20° C. / h, and the temperature is kept for 1 hour. The temperature is then increased to 1100° C. at a heating rate of 40° C. / h, and the temperature is kept for 2 hours. A three-dimensional network structure of C-V2AlC is generated in situ to obtain a carbon crucible.

[0042] Embodiment 2:

[0043] An energy-saving and long-life carbon crucible is prepared by high-temperature carbonization of the following raw materials in parts by weight:

[0044] 30 parts of low carbon earthy graphite coarse aggregate with a particle size of 1mm to 3mm, 25 parts of low carbon earthy graphite fine aggregate with a particle size of 0.08mm to 1mm, 25 parts of low carbon earthy graphite fine powder with a particle size of 200 to 600 meshes, 2 parts of conditioning additives, and 10 parts of epoxy resin modified phenolic resin binder;

[0045] The additive preparation consists of 27 parts by weight of aluminum powder, 51 parts by weight of vanadium powder, 63 parts by weight of vanadium carbide and 12 parts by weight of benzopyrene.

[0046] A method for preparing an energy-saving and long-life carbon crucible comprises the following steps:

[0047] S1. Add low carbon earthy graphite fine powder and conditioning additives into a high-speed mixer and premix for 30 minutes to obtain a batch material;

[0048] S2, the premixed batch material in step S1 is loaded into a high-speed ball mill, and deionized water of 30% of the batch material mass is added into the high-speed ball mill, followed by drying and granulation by a high-speed spray granulation device, the air temperature of the spray granulator is 220°C, and the particle size of the granulated material is 0.8mm, and then the material is sealed and trapped at a temperature of 30°C for 24 hours to obtain the granulated material;

[0049] S3, premixing the low carbon earthy graphite aggregate with half of the epoxy resin modified phenolic resin binder at 60° C. for 30 min, adding the granulated material prepared in step S2, mixing at 80° C. for 30 min, continuing to add the remaining half of the epoxy resin modified phenolic resin binder, mixing at the same temperature for 60 min, to obtain a uniform mixture;

[0050] S4, drying the mixture obtained in step S3 at a temperature of 180° C. and a humidity of 2% for 5 h, and sealing the mixture for 36 h to obtain a formed mixture;

[0051] S5, putting the mixed material obtained in step S4 into an extruder to obtain a carbon crucible blank, and then isostatically pressing the ceramic tube blank obtained by extrusion molding to obtain a dense and uniform carbon crucible blank, and the isostatic pressing pressure is 200 MPa;

[0052] S6. The carbon crucible blank obtained in step S5 is placed in a high-temperature furnace, which is an internal series carbonization furnace. The carbonization is carried out under the protection of a nitrogen atmosphere, so that a layer of carbon nitride is formed on the surface of the sagger to improve the ability of the sagger to resist hydrogen corrosion. The temperature is increased to 300° C. at a heating rate of 20° C. / h, and the temperature is kept for 1 hour. The temperature is then increased to 1100° C. at a heating rate of 40° C. / h, and the temperature is kept for 2 hours. A three-dimensional network structure of C-V2AlC is generated in situ to obtain a carbon crucible.

[0053] Embodiment three:

[0054] An energy-saving and long-life carbon crucible is prepared by high-temperature carbonization of the following raw materials in parts by weight:

[0055] 25 parts of conductive carbon black coarse aggregate with a particle size of 1mm to 3mm, 25 parts of conductive carbon black fine aggregate with a particle size of 0.08mm to 1mm, 30 parts of conductive carbon black fine powder with a particle size of 200 to 600 mesh, 2 parts of tempering additives, and 10 parts of water-soluble binder;

[0056] The modulated additive consists of 27 parts by weight of aluminum powder, 51 parts by weight of vanadium powder, 63 parts by weight of vanadium carbide and 12 parts by weight of benzopyrene.

[0057] A method for preparing an energy-saving and long-life carbon crucible comprises the following steps:

[0058] S1. Add conductive carbon black fine powder and quenching and tempering additives into a high-speed mixer and premix for 30 minutes to obtain a batch;

[0059] S2, the premixed batch material in step S1 is loaded into a high-speed ball mill, and deionized water of 35% of the batch material mass is added into the high-speed ball mill, followed by drying and granulation by a high-speed spray granulation device, the air temperature of the spray granulator is 200°C, and the particle size of the granulated material is 0.8mm, and then the material is sealed and trapped at a temperature of 30°C for 24 hours to obtain the granulated material;

[0060] S3, premixing the conductive carbon black aggregate with half of the Arabic resin binder at 80° C. for 30 min, adding the granulated material prepared in step S2, mixing at 100° C. for 30 min, continuing to add the remaining half of the Arabic resin binder, mixing at the same temperature for 60 min, to obtain a uniform mixture;

[0061] S4, drying the mixture obtained in step S3 at a temperature of 220° C. and a humidity of 2.5% for 5 h, and sealing the mixture for 36 h to obtain a formed mixture;

[0062] S5, putting the mixed material obtained in step S4 into an extruder to obtain a carbon crucible blank, and then isostatically pressing the ceramic tube blank obtained by extrusion molding to obtain a dense and uniform carbon crucible blank, and the isostatic pressing pressure is 200 MPa;

[0063] S6. The carbon crucible blank obtained in step S5 is placed in a high-temperature furnace, which is an internal series carbonization furnace. The carbonization is carried out under the protection of a nitrogen atmosphere, so that a layer of carbon nitride is formed on the surface of the sagger to improve the ability of the sagger to resist hydrogen corrosion. The temperature is increased to 350° C. at a heating rate of 25° C. / h, and the temperature is kept for 1 hour. The temperature is then increased to 1200° C. at a heating rate of 40° C. / h, and the temperature is kept for 2 hours. A three-dimensional network structure of C-V2AlC is generated in situ to obtain a carbon crucible.

[0064] Comparative Example:

[0065] A carbon crucible is prepared by high-temperature carbonization of the following raw materials in parts by weight:

[0066] 80 parts of activated carbon powder with a particle size of 200-600 mesh and 10 parts of phenolic resin binder.

[0067] The preparation method comprises the following steps:

[0068] S1. Mix high carbon earthy graphite powder and phenolic resin binder at 80° C. for 1.5 h to obtain a uniform mixture;

[0069] S2, drying the mixture obtained in step S1 at a temperature of 200° C. and a humidity of 3% for 5 h, and sealing the mixture for 36 h to obtain a formed mixture;

[0070] S3, forming the mixed material obtained in step S2 by friction forming to obtain a carbon crucible blank;

[0071] S6. Place the carbon crucible blank obtained in step S5 in a high-temperature furnace, a box-type carbonization furnace, and perform carbonization under the protection of a nitrogen atmosphere. Heat the temperature to 1200° C. at a heating rate of 60° C. / h, and keep the temperature for 2 hours to obtain a carbon crucible.

[0072] The mechanical properties, thermal shock stability and wettability of the carbon saggers in Examples 1 to 3 and the comparative example were tested, and the test results are as follows:

[0073]

[0074] Among them, the compressive strength is the cold compression strength at room temperature, and the testing standard is GB / T1431-2019; the thermal expansion coefficient is the linear thermal expansion coefficient between 20℃ and 300℃, and the testing standard is YS / T 63.4-2006; the thermal shock cracking experiment is the residual strength retention rate after water cooling at 1000℃, and the testing standard is YB 4018-91; the wettability test is to use a CCD camera to observe the relationship between the changes of the eroded material on the crucible surface and the temperature during the heating process from room temperature to 900℃ under a protective atmosphere.

[0075] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An energy-saving and long-life carbon crucible, It is characterized in that It is prepared by high temperature carbonization of the following raw materials in parts by weight: 10-50 parts of carbon coarse aggregate, 20-35 parts of carbon fine aggregate, 15-40 parts of carbon fine powder, 0.01-3 parts of preparation additives, 3-25 parts of water-soluble binder; The modulated additive is composed of 20 to 30 parts by weight of aluminum powder, 40 to 60 parts by weight of vanadium powder, 50 to 70 parts by weight of vanadium carbide and 10 to 20 parts by weight of benzopyrene; The carbon coarse aggregate and the carbon fine aggregate are one or more of low-carbon earthy graphite, conductive carbon black, activated carbon and asphalt, the particle size of the carbon coarse aggregate is 1mm to 3mm, and the particle size of the carbon fine aggregate is 0.08mm to 1mm; The carbon fine powder is one or more of low-carbon earthy graphite, conductive carbon black, activated carbon and asphalt, and the particle size of the carbon fine powder is 200-600 meshes; The water-soluble binder is one or more of furfural resin, epoxy resin-modified phenolic resin, arabic resin, lignin, polyvinyl alcohol and phosphate; The method for preparing the energy-saving and long-life carbon crucible comprises the following steps: S1. Add the carbon fine powder and the modulated additives into a high-speed mixer and premix for 15 minutes to 12 hours to obtain a batch material; S2, loading the premixed batch materials in step S1 into a high-speed ball mill, adding 5% to 50% of the mass of the batch materials with deionized water into the high-speed ball mill, and then drying and granulating with a high-speed spray granulation equipment to obtain granulated materials; S3, premix the carbon coarse aggregate, carbon fine aggregate and half of the water-soluble binder at 25°C to 200°C for 15 min to 12 h, add the granulated material prepared in step S2, mix at 25°C to 280°C for 15 min to 12 h, continue to add the remaining half of the water-soluble binder, mix at the same temperature for 15 min to 12 h, and obtain a uniform mixture; S4, drying and trapping the mixture prepared in step S3 to obtain a formed mixture; S5, putting the mixed material obtained in step S4 into an extruder to obtain a carbon crucible blank, and then isostatically pressing the ceramic tube blank obtained by extrusion molding to obtain a dense and uniform carbon crucible blank; S6, placing the carbon crucible blank obtained in step S5 in a high temperature furnace, keeping it at 200°C to 400°C for 0.5h to 2h, and keeping it at 800°C to 1200°C for 1h to 2h, and generating CV in situ 2 The three-dimensional network structure of AlC gives a carbon crucible.

2. The energy-saving and long-life carbon crucible according to claim 1, It is characterized in that In step S2, when spray drying granulation is performed, the air temperature of the spray granulator is 150°C to 300°C, and the particle size of the granulated material is 0.001mm to 1.5mm, and then the material is sealed and trapped at a temperature of 28°C to 32°C for 12h to 36h.

3. The energy-saving and long-life carbon crucible according to claim 1, It is characterized in that In step S4, the conditions for drying the mixed material are: temperature 25°C to 350°C, humidity 1% to 15%, drying time 2h to 25h, and sealing time 12h to 48h.

4. The energy-saving and long-life carbon crucible according to claim 1, It is characterized in that In step S5, the isostatic pressure is 150 to 200 MPa.

5. The energy-saving and long-life carbon crucible according to claim 1, It is characterized in that In step S6, the high temperature furnace is one of an Acheson carbonization furnace, an inner string carbonization furnace, a box-type carbonization furnace and a continuous carbonization furnace.

6. The energy-saving and long-life carbon crucible according to claim 1, It is characterized in that In step S6, carbonization is carried out under the protection of vacuum, nitrogen, carbon-buried or argon atmosphere, and the temperature is increased to 200°C to 400°C at a heating rate of 5°C / h to 30°C / h, and then to 800°C to 1200°C at a heating rate of 10°C / h to 60°C / h.